11 Robotic Left Lower Sleeve Lobectomy with Bronchoplasty for the Removal of a Carcinoid Tumour. (28th February 2022) - Tan, G.; Dunning, J.
Abstract: Lung carcinoid tumours constitute approximately 1–2% of all pulmonary tumours. They are derived from enterochromaffin cells, which are also known as 'Kulchitsky cells' and generally have indolent growth and development patterns. Carcinoid tumours are categorized as typical or atypical, depending on the number of mitoses per high power field and the presence of necrosis. In terms of management, surgical resection has been recognized to be the standard treatment for pulmonary carcinoid tumours. To our knowledge, the da Vinci system and robotic surgery have not been applied in sleeve lobectomies and bronchoplasty for the removal of carcinoid tumours in the United Kingdom. Therefore, we present a case of a sleeve lobectomy with bronchoplasty procedure for the removal of a carcinoid tumour located in the left lower lobe of the patient. The bronchus was repaired using a V-lock suture & Prolene sutures with the surgery performed using the da Vinci robotic surgical system.